(3QSGdI aj GdMK Ydi GdPcQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3CeG HYO aEf ef TeQ Yf SGb GdLO GdHdhZ Edi eQJHI GdhGUdjf adjbUO HSdGe PcQ Gddg JYGdi s
(3BNQgG (B:s
(3hcd eLGgOI JJe ai OQLGJgG fhY ef GdeTGgOI habfG Gddg Hcd Pdc MJi jHdZ efg efRd GdScjfI Hefg hLhOg hSYI QMeJg hGdMeO dd QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQJH GdGHLOi e GdBUajI HMjOQ CHGO (B(41(11)) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs